Effectiveness of pictorial health warning on cigarette packages : A cross-sectional study in Sarawak, Malaysia - Rahman, M.M.; Arif, M.T.; Abd Razak, M.F.; Suhaili, M.R.; Tambi, Z.; Akoi, C.; Gabriel, Bain M.; Hussain, H. (Academy of Family Physicians of Malaysia, 2016)
effective and low-cost method for increasing the knowledge and awareness among the community. Thus, a study was conducted to assess the perception of pictorial health warnings (PHWs) against smoking among the adult rural population of Sarawak. Methods: Cross-sectional data were collected from 10 villages in Kota Samarahan and Kuching Division by face to face interview using modified Global Adult Tobacco Survey questionnaire. Nonprobability sampling method was adopted to select the villages. All the households of the selected villages were visited and an adult member was selected randomly from each house irrespective of the sex. After missing value imputation, 1000 data were analysed using statistical software IBM SPSS 20.0 version. Results: Analysis showed that 28.8% of the respondents were current smokers, 7.8% were past smokers and the rest were non-smokers. Six items of pictorial health warnings were evaluated with five point Likert’s scales for attractiveness, fearfulness and adequacy of the information. Analysis revealed that the majority of the respondents had perceived awareness on PHWs, but the smokers believed that this was not adequate to make them quit smoking. Only one-fifth (19.7%) of them reported that current pictorial health warnings were sufficient to motivate people to quit smoking. Conclusion: Though the PHWs on cigarette packages are appealing, it is not sufficient as a reason to stop smoking. Thus, an approach using an integrated anti-tobacco public health programme should be focused into the specific targeted community.